Concordance between cancer gene alterations in tumor and circulating tumor DNA correlates with poor survival in a real‐world precision‐medicine population - Shai Rosenberg; Gil Ben Cohen; Shumei Kato; Ryosuke Okamura; Scott M. Lippman; Razelle Kurzrock (Molecular Oncology, 2023)
Genomic analysis, performed on tumoral tissue DNA and on circulating tumor DNA (ctDNA) from blood, is the cornerstone of precision cancer medicine. Herein, we characterized the clinical prognostic implications of the concordance of alterations in major cancer genes between tissue‐ and blood‐derived DNA in a pan‐cancer cohort. The molecular profiles of both liquid (Guardant Health) and tissue (Foundation Medicine) biopsies from 433 patients were analyzed. Mutations and amplifications of cancer genes scored by these two tests were assessed. In 184 (42.5%) patients, there was at least one mutual gene alteration. The mean number of mutual gene‐level alterations in the samples was 0.67 per patient (range: 0–5). A higher mutual gene‐level alteration number correlated with shorter overall survival (OS). As confirmed in multivariable analysis, patients with ≥2 mutual gene‐level alterations in blood and tissue had a hazard ratio (HR) of death of 1.49 (95% confidence interval [CI]=1–2.2; P=0.047), whereas patients with ≥3 mutual gene‐level alterations had an HR of death 2.38 (95% CI=1.47–3.87; P=0.0005). Together, our results show that gene‐level concordance between tissue DNA and ctDNA analysis is prevalent and is an independent factor predicting significantly shorter patient survival.